How CEO Ethical Leadership Influences Top Management Team Creativity: Evidence From China - Zhao, Jinguo; Sun, Wei; Zhang, Shujie; Zhu, Xiaohong (Frontiers in Psychology, 2020)
The creative thinking and ability of top management team members is important in coping with rapid changes in the external environment and improving the competitive advantage of an organization. This research focuses on the CEO–TMT interface to explain how CEOs influence TMT characteristics, which in turn affects TMT outcomes. Based on social learning theory, this study examines the associations among CEO ethical leadership, TMT cohesion and TMT creativity in a Chinese context using a total of 91 top management teams. To verify the reliability and validity of the constructs, a series of confirmatory factor analyses (CFAs) were run. The results showed that the hypothesized model captured distinct constructs and fits the data well. Multistep regression method was used to test hypotheses. The results indicated that (a) CEO ethical leadership has a positive effect on TMT creativity; (b) TMT cohesion plays a mediating role in the relationship between CEO ethical leadership and TMT creativity; and (c) power distance plays a moderating role in the relationship between CEO ethical leadership and TMT creativity. The greater the power distance, the weaker the positive relationship between CEO ethical leadership and TMT creativity. This study demonstrates the value of CEO ethical leadership and advocates the importance of establishing team cohesion and building a psychologically safe environment to motivate top managers within an organization to share information and knowledge to improve creativity.